Evolution of accessory bones in cetacean skull coupled with decreasing rate of ossification of cranial sutures - Valeriia Telizhenko; Pavel Gol’din (Scientific Reports)
Abstract The skulls of cetaceans (whales, dolphins and porpoises) are distinguished by incomplete ossification of cranial sutures during their lifetime. We suggested suture ossification may correlate with the evolution of rarely reported accessory bones and examine the evolutionary patterns of cranial suture ossification and the presence of accessory elements in the skulls of 47 cetacean species and, for comparison, 15 terrestrial artiodactyls (even-hoofed mammals). A strong phylogenetic signal was found for both suture ossification rate and accessory bone presence. Cetaceans were shown to have a lower ossification rate than most terrestrial artiodactyls, except deer (Cervidae) and mouse deer (Tragulidae), which showed somewhat similar patterns. There were also several types of accessory bony elements, some of them first reported in the skulls of cetaceans and in one case, a muntjac deer. These elements (bones and clefts) evolved in the crania with the least number of ossified sutures. They can be identified as novel elements or, some of them, as plesiomorphies rarely seen in mammals but existing in reptiles and other ancestral groups. This leads to breaking a general trend of mammalian evolution: a reversal of Williston’s law (reduction in bone number) and the development of new accessory cranial bones. Slowing cranial development rates explain these trends, and feeding mechanics may be a driver of decreasing suture ossification in cetaceans.